Multimorbidity in asthma, association with allergy, inflammatory markers and symptom burden, results from the Swedish GA2LEN study. Issue 2 (25th October 2020) - Blöndal, Viiu; Malinovschi, Andrei; Sundbom, Fredrik; James, Anna; Middelveld, Roelinde; Franklin, Karl A.; Lundbäck, Bo; Janson, Christer
Abstract: Background: Asthma is common worldwide and a large part of subjects with asthma have concomitant allergic multimorbidity in the form of rhinitis and/or eczema. Objective: The aim of this study is to investigate whether the presence of allergic multimorbidity in asthma relates to allergic sensitization, allergic and respiratory symptoms, quality of life, inflammatory markers, lung function, use of medication and background factors. Methods: A total of 437 asthmatics from the (GA 2 LEN) cross‐sectional survey in Sweden were grouped depending on the presence of rhinitis and/or eczema. The impact of allergic multimorbidity was assessed in terms of allergic sensitization, allergic and respiratory symptoms, quality of life, type‐2 inflammatory markers (exhaled nitric oxide, eosinophil activation markers, periostin), lung function, use of medication and background factors. Results: Subjects with asthma, rhinitis and eczema were more likely to be sensitized to seasonal allergens (67% vs 32%, P < .001), food allergens (54% vs 18%, P < .001) and to have a higher degree of sensitization than subjects with only asthma (23% vs 10%, P < .001). Subjects with allergic multimorbidity more often had allergic reactions to food (28% vs 10%, P = .002), more respiratory symptoms and anxiety/depression (40% vs, 14%, P < .001) than subjects with only asthma, despite having similar levels of type 2 inflammatory markers. Individuals with allergic multimorbidity were more likely to be diagnosed with asthma before the age of 12 (48% vs 27%, P = .016) and to have maternal heredity for allergy (53% vs 33%, P = .011) than subjects with only asthma. Conclusion and clinical relevance: Asthmatics with allergic multimorbidity are more likely to be sensitized to seasonal aeroallergens, food allergens and they have a higher degree of sensitization compared with those with only asthma. Allergic multimorbidity is associated with respiratory and allergy symptoms, anxiety and/or depression.